A Comparison of Adolescent versus Young Adult Outpatients with First-Presentation Borderline Personality Disorder: Findings from the MOBY Randomized Controlled Trial. (January 2022) - Chanen, Andrew M.; Betts, Jennifer K.; Jackson, Henry; Cotton, Sue M.; Gleeson, John; Davey, Christopher G.; Thompson, Katherine; Perera, Sharnel; Rayner, Victoria; Chong, Sinn Yuin; McCutcheon, Louise
Objective: The increasing focus on adolescent personality disorder has tended to ignore evidence of the developmental continuity of the period from puberty to young adulthood. This study aims to: (1) describe the characteristics of a sample of young people with borderline personality disorder (BPD) who had no previous history of evidence-based treatment for the disorder and (2) compare their characteristics by participant age group. Methods: One hundred and thirty-nine young people (15 to 25 years) with BPD, newly enrolled in the Monitoring Outcomes of BPD in Youth randomized controlled trial, completed semi-structured interview and self-report measures assessing demographic, clinical, and functional characteristics. Younger (aged 15 to 17 years; n = 64) and older (aged 18 to 25 years; n = 75) participants were compared on these same variables using t -tests, chi-square tests, and logistic regression. Results: Young outpatients with BPD had extensive and severe psychopathology and were functioning poorly. Adolescents and young adults with BPD showed substantial similarities on 20 key aspects of their presentation. Significant between-groups differences were observed in household makeup, treatment history, antisocial personality disorder, emotion dysregulation, substance use, age of commencement and extent of self-harm, and achievement of age-appropriate educational milestones. Adolescent BPD group membership was predicted by family composition and self-harm, whereas young adult BPD group membership was predicted by not achieving age-appropriate milestones, vocational disengagement, and emotion dysregulation. The final model explained 54% of the variance and correctly classified 80.2% of the sample by age. Conclusions: Both adolescents and young adults with early stage BPD present with severe and often similar problems to one another, supporting developmental continuity across this age range. However, there are also meaningful differences in presentation, suggesting that pathways to care might differ by age and/or developmental stage. Detection and intervention for personality disorder should not be delayed until individuals reach 18 years of age.